Über den Zeitpunkt und die Ursachen erster Ansätze zur Modifikation der Kriegszielplanung und der Okkupationspolitik Hitlerdeutschlands (Herbst 1942 bis Frühjahr 1943) [On the timing and causes of the first attempts to modify the war objectives planning and the occupation policy of Hitler's Germany (autumn 1942 to spring 1943)] - Nestler, Ludwig (Studia Historiae Oeconomicae, 1979)
This article examines the timing and causes of the first conceptual considerations within the Nazi leadership regarding modifications to their war aims and occupation policies between autumn 1942 and spring 1943. The point of departure is the recognition that Nazi occupation policy was fundamentally shaped both by long-term war objectives and by the rapidly deteriorating military situation of the Axis powers from 1941/42 onward. The study aims to analyze the political shift within key institutions of the Third Reich and to show how military setbacks – particularly the failure of the summer offensive of 1942 and the defeat at Stalingrad –triggered a strategic rethinking. Drawing on numerous archival sources and memoranda, the article identifies early attempts to respond to new realities through adjustments in occupation policy, propaganda strategy, and foreign policy maneuvers. The analysis reveals that by autumn 1942, certain strategy papers and public statements by leading officials (including Goebbels and Rosenberg) indicated a partial retreat from radical colonial and exploitative policies. Instead, proposals emerged for political and tactical concessions, ideological realignment (particularly through intensified anti-communist rhetoric), and more nuanced approaches to leveraging nationalist forces in occupied territories.Nestler’s study makes it clear that these adjustments did not represent a renunciation of imperial ambitions, but rather an attempt to preserve them under altered conditions. Ultimately, the conceptual shift was limited in scope and largely abandoned after the failure of the summer offensive in 1943.